Fast-diffusing receptor collisions with slow-diffusing peptide ligand assemble the ternary parathyroid hormone–GPCR–arrestin complex - Jonathan Pacheco; Karina A. Peña; Sofya Savransky; Alexandre Gidon; Gerald R. V. Hammond; John Janetzko; Jean-Pierre Vilardaga (Nature Communications)
Abstract The assembly of a peptide ligand, its receptor, and β-arrestin (βarr) into a ternary complex within the cell membrane is a crucial aspect of G protein-coupled receptor (GPCR) signaling. We explore this assembly by attaching fluorescent moieties to the parathyroid hormone (PTH) type 1 receptor (PTH1R), using PTH as a prototypical peptide hormone, along with βarr and clathrin, and recording dual-color single-molecule imaging at the plasma membrane of live cells. Here we show that PTH1R exhibits a near-Brownian diffusion, whereas unbound hormone displays limited mobility and slow lateral diffusion at the cell surface. The formation of the PTH–PTH1R–βarr complex occurs in three sequential steps: (1) receptor and ligand collisions, (2) phosphoinositide (PIP3)-dependent recruitment and conformational change of βarr molecules at the plasma membrane, and (3) collision of most βarr molecules with the ligand-bound receptor within clathrin clusters. Our results elucidate the non-random pathway by which PTH–PTH1R–βarr complex is formed and unveil the critical role of PIP3 in regulating GPCR signaling.